Optimization of animal drawn tillage implement systems: Part 2, Development of a reversible plough and a ridger - Gebresenbet, G.; Zerbini, E.; Astatke, A.; Kaumbutho, P. (Elsevier, 1997)
The design and development of a reversible animal-drawn plough and a ridger is presented. The plough was developed on the basis of laboratory experiments reported earlier to determine optimum parameters for acurved implement. The basic design principles of conventional mouldboard ploughs and an ard were taken into consideration. A safety mechanism was developed which was a shear bolt. Apart from the share point, all components of the plough were made from wood, and the total mass was about 10 kg. The orientational parameters of the developed implement such as the tail angle, rake angle and the side-rake angle can be varied to suit the required soil operations and the pulling capability of the draught animals. The developed plough can also be used as a ridger by mounting an extra wing on the plough. Comparative field experiments were conducted in cooperation with the International Livestock Research Institute. ILRI, using the developed and traditional ard-type plough in Ethiopia. Tests were carried out in fields under various soil conditions using oxen and cows. The results showed that the draught required by the developed plough was about 30 percent less than the draught of the traditional Ethiopian ard. A frequency analysis was made to determine the dominant frequencies of the reversible plough under working conditions. The identified frequencies were 0.5, 1.3 and 3.3 Hz. Preliminary assessments were made to compare the performances of a pair of cows with a pair of oxen in relation to speed and forces when pulling the developed plough. A pair of cows moved faster (an average of 0.84 m/s) than the pair of oxen (an average of 0.63 m/s) and exerted proportionally greater pulling forces when operating in the same field. The difference in speed is explained by the greater body weight of the cows and the correspondingly greater pull that could be exerted.